Pandangan Filsafat Islam Terhadap Konsep Pengetahuan - Irfan Rizaldi, Muhammad; Rizanda, Alya; Puspika Sari, Herlini (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2024)
The Islamic philosophical view of the concept of knowledge offers a holistic understanding by combining the roles of reason and revelation as the main sources of gaining knowledge. In the Islamic tradition, reason is used to analyze physical and metaphysical reality, while revelation provides transcendent knowledge about God and moral law. Muslim philosophers such as Al-Farabi, Ibn Sina, Al-Ghazali, and Ibn Rushd, provide different views on how to gain knowledge and the roles of reason and revelation. This study aims to explore the concept of knowledge in Islamic philosophy, including the types of knowledge, its sources. The results of this study indicate that Islamic philosophy is not only relevant in the context of science, but also in answering the challenges of ethics and spirituality in the modern era. A balanced approach between reason and revelation provides a strong foundation for human efforts to achieve more complete knowledge, both in intellectual and moral aspects.